2021
DOI: 10.1038/s41598-021-88731-5
|View full text |Cite
|
Sign up to set email alerts
|

A multi-factorial mathematical model for the selection of electropolishing parameters with a view to reducing the environmental impact

Abstract: Electrochemical metal processing is a process that generates harmful pollution. An important goal often disregarded by researchers is not only the achievement of the best possible quality of electropolished surface, but also minimising the load of metal ions in the wastewater generated in the process. The conducted experiments on the electropolishing of stainless steel in laboratory conditions, varied time, temperature and current density conditions, as well as process bath contamination (ranging from 0 to 6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…1(c) and (d) show the ph and specific gravity of each electrolyte, and it is confirmed that the ph and specific gravity of each electrolyte increase as the usage time of the electrolyte increases. since the electrolyte used for a long time has a high metal ion concentration, the amount of hydrate formed during the electropolishing process also increases [15]. These hydrates were accumulated in the electrolyte in the form of sludge, and the ph and specific gravity increased as impurities in the specimen were mixed with the electrolyte during electropolishing.…”
Section: Resultsmentioning
confidence: 99%
“…1(c) and (d) show the ph and specific gravity of each electrolyte, and it is confirmed that the ph and specific gravity of each electrolyte increase as the usage time of the electrolyte increases. since the electrolyte used for a long time has a high metal ion concentration, the amount of hydrate formed during the electropolishing process also increases [15]. These hydrates were accumulated in the electrolyte in the form of sludge, and the ph and specific gravity increased as impurities in the specimen were mixed with the electrolyte during electropolishing.…”
Section: Resultsmentioning
confidence: 99%
“…One example is the electroplating industry which releases wastewater mainly from the production and processing of metal products. One of the techniques used to treat stainless steels is electropolishing [10][11][12][13][14] . This process is designed to change the surface properties of an object in order to improve its aesthetic value by smoothing and making the surface glossy and at the same time increasing its corrosion resistance 12,[15][16][17][18][19] .…”
mentioning
confidence: 99%
“…One of the techniques used to treat stainless steels is electropolishing [10][11][12][13][14] . This process is designed to change the surface properties of an object in order to improve its aesthetic value by smoothing and making the surface glossy and at the same time increasing its corrosion resistance 12,[15][16][17][18][19] . This method has many applications including food, automotive, and medical industries [20][21][22] .…”
mentioning
confidence: 99%